Pengaruh Disiplin Kerja terhadap Kinerja Perangkat Desa Kecamatan Gunungsitoli Idanoi - Sonitehe Gea; Victorinus Laoli (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2020)
This research was conducted in the Tetehosi II Village Gunungsitoli Idanoi Subdistrict by raising the title: "The Effect of Work Discipline on Village Apparatus Performance in the Tetehosi II Village Gunungsitoli Idanoi Subdistrict". In this study, researchers took a sample of 25 people, all employees in the Tetehosi II Village Office, Gunungsitoli Idanoi Subdistrict. Then the type of data used by researchers in this study are primary data and secondary data. In obtaining research data sources is to use alar and the type of research the author uses is quantitative. Based on the description above, statistically the authors propose the following research results: From the results of the calculation of the validity test of variables X and Y on each item / item questionnaire as many as 20 questions after correlating the results are valid so that the questionnaire / questionnaire is feasible to be used in data processing. This was done by the researcher to check the results of the questionnaire returned by the respondent whether it was in accordance with the instructions given. Based on the hypothesis testing criteria it turns out that Ha was accepted and Ho was rejected where Ha had a relationship and Ho had no relationship, because t arithmetic = 3.091> t table = 2.052 so it can be stated the influence of Work Discipline (X) on Performance (Y) at the Village Office in Gunungsitoli Idanoi District.